INTRA CORRELATION DESTRUCTION TECHNIQUEFOR ENCRYPTION DATA - Mazher, Alaa (Iraqi Journal of Science, 2024)
The need for efficient technique for data encryption is clear. Our attention will be devoted to design hybrid technique which, consists of simple and efficient methods such as RLE, vector substitution, and matrix operations. The adopted technique consists of three stages. Each stage contains a specific tool that is suitable for varied type of data such as text, image, and video .In first stage, different methods could be applied depending on the source data format: applying Run Length Encoding (RLE) and Addition Neighboring Element (ANE) to the image, audio and video, while pattern matching is applied to text file format . Stage two involves matrix manipulation and rotation. Element substitution is implemented to the matrix in third stage; a key substitution matrix is used for the process of substituting elements of the matrix. The key matrix will be sent to the destination receiver in order to enable him or her to reconstruct the original data. Finally it must be mentioned that a good result have been obtained using arbitrary plain text and standard image (Leena), where some investigations proved that it is so hard to break the encrypted data.